2022
DOI: 10.3389/fphar.2022.820760
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Connective Tissue Disease in Pregnancy: A Topic Yet to be Explored

Abstract: Undifferentiated connective tissue disease (UCTD) is characterized by signs and symptoms suggestive of a connective tissue disease (CTD), but not fulfilling criteria for a specific CTD. Although UCTD is probably the most common rheumatic disease diagnosed in pregnant women, data about disease course during pregnancy and perinatal outcomes are very limited. Compared to other CTDs, UCTD seems to have milder clinical manifestations in pregnancy. Its natural history is related to disease activity at conception. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
0
7
0
1
Order By: Relevance
“…Although UCTD is the most common rheumatic disorder diagnosed in pregnant women, 2 data on disease course and maternal-fetal outcomes are limited. One uncontrolled study of 20 pregnant patients with UCTD demonstrated that pregnancy may be a trigger for the development of a defined connective tissue disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although UCTD is the most common rheumatic disorder diagnosed in pregnant women, 2 data on disease course and maternal-fetal outcomes are limited. One uncontrolled study of 20 pregnant patients with UCTD demonstrated that pregnancy may be a trigger for the development of a defined connective tissue disorder.…”
Section: Discussionmentioning
confidence: 99%
“…1 It can appear to have a mild clinical course and is marked by the absence of severe organ damage or involvement. 1 , 2 Pregnancy represents a possible trigger for the development of a connective tissue disorder; however, the influence of pregnancy on disease course is not well understood. We present the case of a pregnant woman with UCTD with an unusual cutaneous presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Більшість проведених дотепер досліджень у педіатричній практиці щодо НДСТ присвячені вивченню взаємозв'язків між виразністю клініко-біохімічних ознак НДСТ у дітей та підлітків і перебігом диспластикозалежних станів та хвороб [2, 3,10,12,15,16,20,25,26]. Дослідники акушерських аспектів НДСТ акцентують увагу насамперед на рівні захворюваності серед новонароджених від матерів із проявами НДСТ [8,14,22].…”
Section: вступunclassified
“…During pregnancy, patients with autoimmune rheumatic diseases often refuse treatment since they think drug administration would cause any damage to their future babies, Tincani reported. Moreover, there are evidence showing that disease activity in pregnancy could cause an increase in both fetal and maternal complications as demonstrated by Mecacci et al [ 167 ]. While only some drugs such as methotrexate, cyclophosphamide, and mycophenolate have teratogenic activities; their use in pregnancy is limited and most of the therapeutic agents used in autoimmune rheumatic diseases do not cause any malformations but may have few pregnancy complications [ 168 ].…”
Section: Pregnancy and Pediatrics During Auto13mentioning
confidence: 99%